2023
DOI: 10.3390/su16010162
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Organic Fertilizers on the Quality, Yield, and Fatty Acids of Maize and Soybean in Southeast Kazakhstan

Maxat Toishimanov,
Zhulduz Suleimenova,
Nurgul Myrzabayeva
et al.

Abstract: This paper presents the effects of organic fertilizers on the yield, quality, and fatty acid composition of maize and soybean in 2022 in Southeast Kazakhstan. Maize and soybean yields were improved by commercial organic fertilizers. In general, the yield, quality, and fatty acid (FA) parameters of both crops were influenced by various types of organic fertilizers. The application of HansePlant fertilizer allowed for an increase in the yield of maize seed by 47% and soybean by 31%. Organic fertilizers improved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Previous studies have shown that the combined application of organic and inorganic fertilizer significantly increased crop yield [30]. Maize and soybean yields were improved by commercial organic fertilizers [31]. Under drip irrigation, the use of organic amendments increased the grape yields [32].…”
Section: Effect Of Organic Fertilizer On Grape Yieldmentioning
confidence: 98%
“…Previous studies have shown that the combined application of organic and inorganic fertilizer significantly increased crop yield [30]. Maize and soybean yields were improved by commercial organic fertilizers [31]. Under drip irrigation, the use of organic amendments increased the grape yields [32].…”
Section: Effect Of Organic Fertilizer On Grape Yieldmentioning
confidence: 98%
“…The primary measures for the development of organic farming here may be the production of organic corn due to its minimum transpiration coefficient (300) among all cultivated cereals and the insignificant response of the crop to soil fertility. Production experiments in the Almaty region showed an almost 50% increase in the corn harvest when using organic fertilizers [87]. In addition, to saturate the domestic market, it is advisable to produce organic vegetables on irrigated lands, potatoes, sweet peppers, onions and garlic, especially the last two crops actively used in the manufacture of Kazakh national dishes, beshparmak and horse sausages (kazy and shuzhuk), respectively.…”
Section: Organic Irrigated Agriculturementioning
confidence: 99%
“…Biologically active compounds released by organic fertilisers have a positive effect on yield and quality indicators, such as fatty acids, vitamins, amino acids, and polypeptides [17]. Organic fertilisers can have an effect on oil content and composition through changes in the availability of nutrients to plants [18].…”
Section: Introductionmentioning
confidence: 99%